Ethnic Fractionalization, Governance and Loan Defaults in Africa - Svetlana Andrianova; Badi H. Baltagi; Panicos Demetriades; David Fielding (Center for Economic Studies and ifo Institute (CESifo), 2014)
We present a theoretical model of moral hazard and adverse selection in an imperfectly competitive loans market that is suitable for application to Africa. The model allows for variation in both the level of contract enforcement (depending on the quality of governance) and the degree of market segmentation (depending on the level of ethnic fractionalization). The model predicts a specific form of non-linearity in the effects of these variables on the loan default rate. Empirical analysis using African panel data for 111 individual banks in 29 countries over 2000-2008 provides strong evidence for these predictions. Our results have important implications for the conditions under which policy reform will enhance financial development.
Keywords: G21; O16; 330; ethnic fractionalization; governance; financial development; African banks; panel data